Bank Air Susu Ibu dalam Perspektif Hukum Islam - Dwi Condro Wulan (Universitas Islam Indonesia, 2022)
Breast milk is the most perfect nourishment that is clean and contains lots of nutrients for babies because the processing is carried out naturally in the mother's body. When a mother is unable to breastfeed for various reasons, breast milk can be obtained from breast milk donors. This fact prompted European scientists to come up with the idea of establishing a breast milk bank which aims to help mothers who cannot breastfeed their babies directly. The purpose of this study is to identify and analyze the breast milk bank in the perspective of Islamic law and Islamic foundations that allow breast milk bank. This study uses the theory of legal certainty and the theory of benefits. The research method in this study uses a juridical approach. The results of this study conclude that first, the basis for the permissibility of breast milk bank is the opinion of Al-Imam asy-Syafi'i who asserted that,